Kandungan Senyawa Fungsional Daun Tanaman Gaharu (Aquilaria malaccensis) Berdasarkan Posisi Daun pada Cabang - Budi Santoso; Berta Sri Kristina Ginting; Tri Wardani Widowati; Aldila Din Pangawikan (Jurnal Ilmu Kehutanan, 2022)
This study aimed to analyze several secondary metabolite compounds that are antioxidants in the leaves of gaharu plants based on the position of the leaves on the branches. The experimental design used was a non-factorial randomized block design. The research treatment consisted of three factors, namely (A1) young leaves (position of 1-4 leaves from the shoot), (A2) medium leaves (position of 5-8 leaves from the shoot), and (A3) old leaves (position of 9-12 leaves from the shoots). The results showed that the position of the leaves on the branch of the gaharu plant significantly affected the number of secondary metabolites produced. Gaharu plant leaves contain secondary metabolites, namely alkaloids 1.65-4.20%, saponins 2.47-4.00%, tannins 0.69-2.70%, total phenol 29.70-54.68 mg/L, and total chlorophyll 9.21-20.03 mg/L. Tannins and total phenols are functional compounds in gaharu leaves which are antioxidants. The antioxidant properties of this leaf are included in the strong category with an IC50 value of 49.30-68.30 mg/L wherein young leaves have higher antioxidant properties than old leaves.